2011
DOI: 10.1002/acr.20510
|View full text |Cite
|
Sign up to set email alerts
|

Luteinized unruptured follicle syndrome increased by inactive disease and selective cyclooxygenase 2 inhibitors in women with inflammatory arthropathies

Abstract: Objective. Administration of nonsteroidal antiinflammatory drugs (NSAIDs) may impair fertility. The occurrence of the luteinized unruptured follicle (LUF) syndrome was assessed in women with inflammatory arthropathies exposed to NSAIDs and compared to that in nonexposed women. Methods. Fourteen patients with inflammatory rheumatic disease, 29 women with noninflammatory musculoskeletal conditions, and 449 women not exposed to NSAIDs were studied by intravaginal ultrasound monitoring for follicular development a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 17 publications
0
27
0
7
Order By: Relevance
“…Inhibition of follicle rupture requires high anti-inflammatory doses of NSAIDs, and selective inhibitors of COX-2 are more potent than non selective inhibitors. 5 However, active rheumatic dis ease might actually reduce the occur rence of LUF syndrome, as shown in a study that compared exposure to NSAIDs in patients with active and inactive rheumatic dis ease. 5 The effect of cortico steroids on fertility is com plex and includes both facilita tory and inhibitory effects on reproduction.…”
Section: Monika øStensenmentioning
confidence: 97%
See 1 more Smart Citation
“…Inhibition of follicle rupture requires high anti-inflammatory doses of NSAIDs, and selective inhibitors of COX-2 are more potent than non selective inhibitors. 5 However, active rheumatic dis ease might actually reduce the occur rence of LUF syndrome, as shown in a study that compared exposure to NSAIDs in patients with active and inactive rheumatic dis ease. 5 The effect of cortico steroids on fertility is com plex and includes both facilita tory and inhibitory effects on reproduction.…”
Section: Monika øStensenmentioning
confidence: 97%
“…5 However, active rheumatic dis ease might actually reduce the occur rence of LUF syndrome, as shown in a study that compared exposure to NSAIDs in patients with active and inactive rheumatic dis ease. 5 The effect of cortico steroids on fertility is com plex and includes both facilita tory and inhibitory effects on reproduction. 6 Theoretic ally, cortico steroids act in several ways: by disturbing the hypothalamic-pituitary-ovarian axis; by inhibiting phos pholipase A2 enzymes '' Can subfertility in female patients with rheumatoid arthritis (RA) be prevented?…”
Section: Monika øStensenmentioning
confidence: 97%
“…Protection of ovarian function can be provided by treatment with gonadotropin-releasing hormone analogues [126]. Women should be informed that NSAIDs may inhibit ovulation, therefore they should stop them at day 8 of the menstrual cycle when they want to conceive [127].…”
Section: Contraception Fertility and Assisted Reproductionmentioning
confidence: 99%
“…Micu et al conducted a prospective study which showed that women receiving nonsteroidal antiinflammatory drugs (NSAIDs) for rheumatic disease had a greater incidence of the LUF syndrome as compared to nonexposed women (35.6 vs 3.4%). 16 Etoricoxib, a COX2 inhibitor, was found to have the most potent effect (75% of all LUF cases) while diclofenac was less significant (15%). Interestingly, there was a much higher frequency of LUF syndrome in patients with inactive rheumatic disease compared with active disease.…”
Section: Case 2: Luteinized Unruptured Folliclementioning
confidence: 98%
“…Interestingly, there was a much higher frequency of LUF syndrome in patients with inactive rheumatic disease compared with active disease. 16 There is an association between LUF syndrome and unexplained infertility, chronic pelvic infections and endometriosis.…”
Section: Case 2: Luteinized Unruptured Folliclementioning
confidence: 99%